2013
DOI: 10.3390/molecules18055891
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from Alternaria Fungi and Their Bioactivities

Abstract: Alternaria is a cosmopolitan fungal genus widely distributing in soil and organic matter. It includes saprophytic, endophytic and pathogenic species. At least 268 metabolites from Alternaria fungi have been reported in the past few decades. They mainly include nitrogen-containing metabolites, steroids, terpenoids, pyranones, quinones, and phenolics. This review aims to briefly summarize the structurally different metabolites produced by Alternaria fungi, as well as their occurrences, biological activities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
217
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(222 citation statements)
references
References 184 publications
1
217
0
4
Order By: Relevance
“…The authors postulated djalonensone to be a significant taxonomic marker of the plant species [48]. However, djalonensone is identical to alternariol 9-methyl ether (AME) which has been isolated from a series of fungi including pathogenic and endophytic fungi [1]. Thus, the significance of djalonensone (11) as an important taxonomic marker of the plant species should be reconsidered.…”
Section: Dibenzo-α-pyrones From Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors postulated djalonensone to be a significant taxonomic marker of the plant species [48]. However, djalonensone is identical to alternariol 9-methyl ether (AME) which has been isolated from a series of fungi including pathogenic and endophytic fungi [1]. Thus, the significance of djalonensone (11) as an important taxonomic marker of the plant species should be reconsidered.…”
Section: Dibenzo-α-pyrones From Plantsmentioning
confidence: 99%
“…After administration of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]acetate and [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]acetate to cultured lichen mycobionts of Graphis spp., acetate units were incorporated into the 6H-dibenzo[b,d]pyran-6-one derivatives including alternariol (10), AME (11) and graphislactones A-F (18-23) [3]. Alternariol (10) could suffer oxidative demethylation at C-1, hydroxylation at C-4, and O-methylation at C-9 to lead formation of graphislactones E (22) and F (23).…”
Section: Biosynthesis and Biotransformationmentioning
confidence: 99%
See 1 more Smart Citation
“…University of Agriculture in Krakow 29 Listopada 54,Poland in the soil (Lou et al, 2013). Many species are saprotrophs, plant pathogens or crop pathogens.…”
Section: Department Of Plant Protecion Faculty Of Biotechnology and Hmentioning
confidence: 99%
“…The genus Alternaria of ascomycete fungi is a major phytopathogen, comprised of 299 species, and it is found throughout the world (Kirk et al, 2008). Over 268 metabolites have been reported from different species of Alternaria, and most of them showed phytotoxic, cytotoxic, and antimicrobial properties (Lou et al, 2013). Sanodiya et al (2010) identified tenuazonic acid in A. alternata and verified its herbicidal potential against parthenium.…”
Section: Introductionmentioning
confidence: 99%